2021
DOI: 10.3390/chemosensors9040084
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated Graphene Nanoribbons for Highly-Selective Ammonia Gas Sensors: Ab Initio Study

Abstract: The character and degree of influence of carboxylic acid groups (COOH) on the sensory properties (particularly on the chemoresistive response) of a gas sensor based on zigzag and armchair graphene nanoribbons are shown. Using density functional theory (DFT) calculations, it is found that it is more promising to use a carboxylated zigzag nanoribbon as a sensor element. The chemoresistive response of these nanoribbons is higher than uncarboxylated and carboxylated nanoribbons. It is also revealed that the wet na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…[45] Moreover, a study by Barkov et al demonstrated that the efficiency of carboxylated graphene nanoribbons in ammonia detection improved almost twofold gas response since ammonia is adsorbed preferably by carboxyl groups. [46] Wang and co-workers synthesized carboxyl functionalized carbon nanocoil for NH 3 sensors and reported an improved sensing response more than twice compared with pristine carbon nanocoil. [47] Therefore, it is noticeably confirmed that the chemical interaction of ammonia gas molecules with carboxyl groups has the potential to detect ammonia gas.…”
Section: Introductionmentioning
confidence: 99%
“…[45] Moreover, a study by Barkov et al demonstrated that the efficiency of carboxylated graphene nanoribbons in ammonia detection improved almost twofold gas response since ammonia is adsorbed preferably by carboxyl groups. [46] Wang and co-workers synthesized carboxyl functionalized carbon nanocoil for NH 3 sensors and reported an improved sensing response more than twice compared with pristine carbon nanocoil. [47] Therefore, it is noticeably confirmed that the chemical interaction of ammonia gas molecules with carboxyl groups has the potential to detect ammonia gas.…”
Section: Introductionmentioning
confidence: 99%
“…They found that graphene modified with Ni6 is more active for ammonia adsorption and dissociation. P. Barkov examined modifying graphene nanoribbons with carboxylic acid (COOH) group and its effect on ammonia adsorption using DFT calculations [31]. They found that wet nanoribbons interact further with ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…They found that graphene modified with Ni 6 is more active for ammonia adsorption and dissociation. Barkov examined modifying graphene nanoribbons with carboxylic acid (COOH) group and its effect on ammonia adsorption using DFT calculations [ 31 ]. They found that wet nanoribbons interact further with ammonia.…”
Section: Introductionmentioning
confidence: 99%